Three-dimensional ultrasonographic assessment of fetal total lung volume as a prognostic factor in primary pleural effusion - Ruano, Rodrigo (2012)
Objectives-The purpose of this study was to predict perinatal outcomes using fetal total lung volumes assessed by 3-dimensional ultrasonography (3DUS) in primary pleural effusion. Methods-Between July 2005 and July 2010, total lung volumes were prospectively estimated in fetuses with primary pleural effusion by 3DUS using virtual organ computer- aided analysis software. The first and last US examinations were considered in the analysis. The observed/expected total lung volumes were calculated. Main outcomes were perinatal death (up to 28 days of life) and respiratory morbidity (orotracheal intubation with mechanical respiratory support >48 hours). Results-Twelve of 19 fetuses (63.2%) survived. Among the survivors, 7 (58.3%) had severe respiratory morbidity. The observed/expected total lung volume at the last US examination before birth was significantly associated with perinatal death (P< .01) and respiratory morbidity (P< .01) as well as fetal hydrops (P< .01) and bilateral effusion (P= .01). Conclusions-Fetal total lung volumes may be useful for the prediction of perinatal outcomes in primary pleural effusion. © 2012 by the American Institute of Ultrasound in Medicine.